New Approach Towards Sustainability – The Global Efficiency Concept (GEff) - Pitis, Dr. Constantin; Carr, Dave; Rasmussen, Greg; Walstra, Cedric (Journal of Environmental Science and Engineering Technology, 2023)
In the actual economical environment, business sustainability requires high-efficiency technological processes and new innovative developments. That is why the efficiency concept has to be present at all levels of industrial and financial activities. The proposed concepts in this paper could be further developed as a model for improving companies’ corporate energy policies. Nowadays, some purchase decisions for equipment are still driven predominately by the purchase price, and the full consequences of energy efficiency and the impact on the environment are not always considered. In general relatively “low value equipment” purchase policy is still driven by purchase price only, in spite of the evidence that such price represents a maximum of 5 % to 7 % of the total expenses related to the total costs of ownership. In the minerals industry “low value equipment”, like low-voltage motors (up to 1100 volts, 50/60 Hz), are found many times and in very large numbers, their efficiency and reliability influencing dramatically specific costs of technological processes. Although with “major equipment” energy savings are considered more in the purchase decision, every growing importance on the environment of “Green House Gas” (GHG) emissions is still not a major factor when selecting equipment. Often more traditional equipment is purchased at the expense of new innovative technologies that in addition to providing energy savings can also be used as a tool for trading Carbon Credits in the financial marketplace. An example of such a technology is the IsaMill™ comminution machine, which is becoming more widely used in gold and general mining operations in South Africa and throughout the world. Comminution in the mining industry is one of the most energy intensive activities in the world, and the innovative use of “major equipment” saving power can also have a positive effect on the environment. The paper presents descriptions of the essentials of the Global Efficiency (GEff) concept that has been promoted over the last years in South Africa. Price-efficiency criteria (as a corollary of GEff) are investigated for applications incorporating equipments that are driven by low and high voltage motors. The paper presents theoretical and technical aspects analysing the economic and environmental impact, by reducing total cost of ownership with energy savings, for one “low value equipment” in typical applications largely used in mineral processing in the gold mining industry, and one “major equipment” purchase at a current operating gold mine where the innovative IsaMill™ comminution technology was installed as an alternative to traditional older technologies. Besides the impact of energy savings with high-efficiency technological processes and new innovative developments, this paper suggests the general impacts of: Technical and economical performance improvements and competitiveness of mining corporations to international standards; Defusing incipient energy crisis in the gold mining sector; Improving environmental conditions; Creating new job opportunities in the gold mining sector.